Association of autism spectrum disorder and gestational diabetes mellitus of mothers in Bangladesh - Khanom, Farzana; Chowdhury, Shahanaz; Ahmed, Sabrina; ., Moniruzzaman; Ahmed, M.S.A. (Indian Journal of Community Health, 2015)
Background: Globally Approximately 1 in 110 children has Autism Spectrum Disorder (ASD) and the cumulative incidence of this disorder seems to be increasing. To date, the etiology of ASD is unknown. Gestational diabetes is a common pregnancy complication whose prevalence is increasing among women of reproductive age and results in both short-and long-term adverse outcomes for the offspring and may contribute to ASD risk. Aims & Objectives: The aim of the study was to determine the association of maternal gestational diabetes mellitus with autism spectrum disorder in children. Material & Methods: A case control study was conducted among the children 5-7 years old diagnosed with an autism spectrum disorder (n=99) in special need primary schools and a similar age control group of children (n= 198) without the disease at randomly selected primary schools. The groups of children were compared with the obstetric information regarding Gestational Diabetes Mellitus (GDM) of mothers during their index pregnancy. Results: Compared with the control subjects, cases had significantly older parents and were more likely to be high socioeconomic status. History of GDM during index pregnancy were higher in cases than controls [OR=2.30, CI= 1.36 – 3.91].Prenatal and perinatal risk factors were more prevalent among case mothers compared with controls. Collectively, these conditions were associated with a higher likelihood of ASD than controls. Among cases family history of DM were more common compared with controls [OR=23, CI= 10.84 – 48.94]. Case mothers had greater frequencies of threatened abortion [OR= 3.23, CI= 1.94- 5.37], bleeding during pregnancy [OR=1.25, CI=0.20–7.61] and more likely to have experienced cesarean section. Male children were more affected by ASD [OR= 2.87, CI= 1.67 – 4.90] compared with controls. Conclusions: Maternal DM in pregnancy is responsible for at least a good proportion of cases of ASD which in turn has been proven as independent risk factors for autism.